Immune thrombocytopenia in patients with chronic lymphocytic leukemia treated with cladribine‐based regiments or chlorambucil – follow‐up of PALG‐CLL randomized trials. (19th April 2013) - Blonski, Jerzy Z.; Robak, Tadeusz; Chojnowski, Krzysztof; Gora‐Tybor, Joanna; Warzocha, Krzysztof; Ceglarek, Bernadetta; Seferynska, Ilona; Calbecka, Malgorzata; Kostyra, Aleksandra; Stella‐Holowiecka, Beata; Kloczko, Janusz; Dmoszynska, Anna; et al.
Abstract Objectives The relationship between treatments of chronic lymphocytic leukemia (CLL) with cladribine (2‐CdA) or chlorambucil and immune thrombocytopenia (IT) has not been yet determined. Methods The records of 777 patients in two randomized Polish Adult Leukemia Group (PALG)‐CLL programs treated with these agents were retrospectively analyzed. Results Immune thrombocytopenia occurred in 55 of 777 (7.1%) patients. No significant differences in IT prevalence were seen between patients on chlorambucil or 2‐CdA‐based regiments (P = 0.33). IT developed at a median time of 0.499 yr (0.06–4.8) from the start of CLL therapy. This time was significantly longer in patients treated with chlorambucil (2.03 yr, 95%CI: 0.06–4.22) in relation to patients treated with 2‐CdA‐based regiments (0.52 yr, 95%CI: 0.34–0.69, P = 0.049). Overall survival (OS) of patients with IT and those without IT were similar (2.65 yr vs. 3.2 yr P = 0.23) but the severity of bleeding was more pronounced in the 2‐CdA group. The responses to IT therapy were 35%, 54% and 75% for steroids, chemotherapy and splenectomy, respectively. Conclusions In this study, an unexpectedly high percentage of IT incidence was demonstrated in patients with CLL requiring chemotherapy. Although no marked differences were seen in IT frequency in patients treated with 2‐CdA‐based regiments compared to chlorambucil regimen, the clinical course of hemorrhagic diathesis was more severe in 2‐CdA group. Also, the time elapsed from study screening to IT diagnosis was significantly shorter in the 2‐CdA group than in the chlorambucil group suggesting a causative relationship. The appearance of IT did not influence the median time of OS.